Three new species of the genus Kisaura Ross (1956) (Trichoptera: Philopotamidae) from Arunachal Pradesh, India - Pandher, Manpreet Singh; Kaur, Simarjit; Parey, Sajad H. (Zootaxa, 2018)
In this paper three new species of the genus Kisaura from Arunachal Pradesh, northeastern India, are described and illustrated. The newly described species are K. sainii sp. n. (from Lumla), K. dirangensis sp. n. and K. vikrami sp. n. (both from Dirang). With these additions the total number of species in the genus from India now stands at 27.